Crime in Marriage: The Practice of Polygamy in the Puncak Sorik Merapi Community, Mandailing Natal - Mustafid mustafid; Risvan Akhir Roswandi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
Polygamy is an option for husbands who can be fair to their wives; a husband cannot take refuge behind religion to legalize polygamy while he cannot do justice. This study aims to look at the crimes of polygamy in Puncak Sorik Marapi Mandailing Natal Regency, North Sumatra Province. This research is qualitative; data were collected by interviewing informants, and secondary data were sourced from journals, books, and documents considered related to this paper. The data obtained were analyzed using descriptive and qualitative data analysis techniques. As for the results of this study, they show that the husband practiced polygamy at Sorik Peak Marapi, committing crimes, namely: first, not providing for his wife's birth, second, abandoning children so that some drop out of school, and third, damaging good relations with wife, children, and wife's family. Husbands do not carry out the provisions set by Islam if they want to have polygamy; that is fair, because Allah has explained in Surah An-Nisa verse 3 that husbands must act fairly if they want to have polygamy. The impact of the husband's injustice was felt by their first wife, who felt the bitterness of life. The wife had to work hard to support herself and their children, and the impact was also felt by the children because they could not continue their schooling with the constraint of having no money. The tendency of husbands to neglect their wives and children tends to bring harm to them.